PENERAPAN MANAJEMEN KINERJ A PADA PT. (PERSERO) ANGKASA PURA I BANDAR UDARA SAM RATULANGI MANADO - Sabuhari, Rahmat (Jurnal MS, 2014)
Modern enterprises , putting the company 's performance should really be measured, giving rise to test rank - performance measurement , therefore need human resource management within the company so that productivity can be increased , which in turn is expected by the company objectives can be achieved . It is called the performance management. Performance management should be able to ascertain the level of success or failure of the company's activities. This research is about how the implementation of performance management at PT . ( Persero ) Angkasa Pura I airport Sam Ratulangi Manado . Therefore the main objective of this study was to determine the extent to which the implementation of performance management . The data used is primary data and secondary data . Primary data were obtained by conducting in-depth interviews with 4 people informant from the corporate office . The analytical method used was a qualitative study using a general inductive approach . It is intended to assist the understanding of the meaning of the data is complicated by the development of the themes outlined in the raw data , and then drawn a conclusion of the interview. The findings of the research showed that employee initiative can be implemented , the role is poorly understood , dependence on superiors quite high , reports are often late , and a leadership style that is applied very supportive of employee performance . Fore expected to socialize leadership to employees in order to understand the implementation of performance management in his company well.